Studi Unjuk Kerja Peralatan Penambangan Nikel Berdasarkan Target Produksi pada Blok EHJ Pit Mawar dan Pit 3 di PT. Bumi Nikel Nusantara Desa Puuuwonua, Kecamatan Andowia, Kabupaten Konawe Utara, Provinsi Sulawesi Tenggara - La Ode Alibin Akbar Tuminda; Endang Hartiningsih; Rahmat Indrajati; Frans Simbol Tambing (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Based on Ministry of Energy and Mineral Resources data, regarding the target achievement of mechanical equipment performance in mining companies, PT Bumi Nikel Nusantara has a level of achievement value of equipment performance less than the value set in the Minister of Energy and Mineral Resources Decree No.1827/2018. A mechanical equipment performance value can be achieved by examining ongoing mining activities on one mining front that includes loading and transportation activities. One of the efforts is to know the productive time, calculate the obstacle time and repair time of the equipment in case of damage. The results of the performance for the Use of Availability (UA) parameter of the EHJ Block Mawar pit loading equipment is 74% (not achieved), 71% Pit Mawar transport equipment, pit 3 loading excavation equipment 75% (achieved), and Pit 3 transport equipment 71% (not achieved). While the results of the study of the achievement of productivity of the loading and unloading equipment show the achievement with a value for loading equipment of 76,71% (not achieved) and transport equipment of 65,63% (not achieved).